2014
DOI: 10.4236/psych.2014.54039
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Questionable Practice of Using Excessive Massively Multiplayer Online Game Play as a Marker of Pathological Video Game Dependence among Adolescent and Young Adult Male Players

Abstract: The present study explored pathological online video game dependence among adolescent and young adult males in the context of excessive massively multiplayer online game (MMOG) play. Psychological criteria distinguishing high engagement from addiction were used, as a means of examining MMOG play in the context of an excessive and addictive activity. This is a distinction that has been lost in the previous research, setting this study apart from other studies investigating frequency of play in the context of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Researchers have recently theorized that large amounts of time spent playing online games reflect players' enjoyment (e.g. a hobby) or as an opportunity for 'flow' (Seok & DaCosta, 2014), rather than being indicative of the consequences associated with problematic MMORPG use per se (Kardefelt-Winther, 2014;Weinstein & Lejoyeux, 2010).…”
Section: The Current Studymentioning
confidence: 99%
“…Researchers have recently theorized that large amounts of time spent playing online games reflect players' enjoyment (e.g. a hobby) or as an opportunity for 'flow' (Seok & DaCosta, 2014), rather than being indicative of the consequences associated with problematic MMORPG use per se (Kardefelt-Winther, 2014;Weinstein & Lejoyeux, 2010).…”
Section: The Current Studymentioning
confidence: 99%
“…"In the modern lifestyle where technology with the inclusion of internet has facilitated man, it can be a possible cause of decreased physical activity" (Cheng & Li, 2014). Digital games can cause a tremendous amount of consequences to the player (Young, 2009;Block, 2008;Seok and DaCosta 2014;Griffiths, 2008). Also, Caplan (2002), suggested that unhealthy technology overuse can be problematic and may have negative consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, time spent online gaming only increased depression ratings and negative relationships with parents when participants were in early adolescence (11–14 years old; Steinberg, 1999). The gender finding could be explained by literature that has found that problematic or addictive online gaming is more common in males compared with females (e.g., Bonnaire & Phan, 2017; Lo et al, 2005; Seok & DaCosta, 2014). The findings regarding age suggest that heavier online gamers in early adolescence are a particularly vulnerable group.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified clear sex and well‐being differences between online gaming and Internet use (e.g., Király et al, 2014). Problematic or addictive online gaming has consistently been found to be more common in males compared with females (e.g., Bonnaire & Phan, 2017; Lo et al, 2005; Seok & DaCosta, 2014). Furthermore, Pontes (2017) found that Facebook addiction and IGD were positively associated with each other (those experiencing one were more likely to experience the other), and both contributed to higher ratings of depression, anxiety, and stress, however, the impact was slightly more pronounced for IGD.…”
Section: Online Gaming and Social Media Usementioning
confidence: 99%